2022
DOI: 10.1016/j.ajogmf.2021.100492
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-neonatal transfer of SARS-CoV-2 immunoglobulin G antibodies among parturient women treated with BNT162b2 messenger RNA vaccine during pregnancy

Abstract: Background The exclusion of pregnant women from COVID-19 mRNA vaccine trials raised hesitancy regarding the benefit of vaccination of pregnant women, hence little is known about the vaccine's efficacy in this population. Objective To determine the maternal-neonatal transplacental transfer of SARS CoV-2 antibodies among vaccinated parturient women. A control group of COVID 19 recovered patients was included in order to compare IgG levels between vaccinated and recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
105
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 24 publications
13
105
1
5
Order By: Relevance
“…We found that the timing of immunization during pregnancy is important to ensure transplacental transfer of protective antibodies to the neonate, and during critical windows of immune vulnerability during early infancy. Consistent with prior studies showing robust immune responses to mRNA vaccination 14,15,17 , we found high levels of IgG after two doses of mRNA vaccine. However, completion of the vaccination series well before delivery was important to ensure transfer of antibodies to the infant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the timing of immunization during pregnancy is important to ensure transplacental transfer of protective antibodies to the neonate, and during critical windows of immune vulnerability during early infancy. Consistent with prior studies showing robust immune responses to mRNA vaccination 14,15,17 , we found high levels of IgG after two doses of mRNA vaccine. However, completion of the vaccination series well before delivery was important to ensure transfer of antibodies to the infant.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to prior studies 14,15,17 , we found that mRNA vaccination during pregnancy led to an increase in anti-SARS-Cov-2 IgG following dose 1 (n=7, mean 388.6, SD 224.8 RFU) and an even further robust increase after vaccination dose 2 (n=12, mean 3214, SD 1383 RFU). Anti-SARS-CoV-2 IgM (n=7, mean 53.3, SD 50.2 RFU) was detected in two maternal participants following dose 1, but only 1 participant following dose 2 (n=12, mean 23.8, SD 17 RFU, Fig 1).…”
Section: Mrna Vaccination In Pregnancy Leads To a Robust Antibody Responsesupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with other recent studies, we have observed that the anti-SARS-CoV-2 vaccine transfers antibody immunity to the fetus through the placental barrier, revealing IgG anti-SARS-CoV-2 on neonatal blood samples [ 11 , 12 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Evidence from other vaccine-preventable diseases suggests that maternal immunization can provide protection to infants, especially during the high-risk first 6 months of life, through passive transplacental antibody transfer (2). Recent studies of COVID-19 vaccination during pregnancy suggest the possibility of transplacental transfer of SARS-CoV-2-specific antibodies that might provide protection to infants (3)(4)(5); however, no epidemiologic evidence currently exists for the protective benefits of maternal immunization during pregnancy against COVID-19 in infants. The Overcoming COVID-19 network conducted a test-negative, case-control study at 20 pediatric hospitals in 17 states during July 1, 2021-January 17, 2022, to assess effectiveness of maternal completion of a 2-dose primary mRNA COVID-19 vaccination series during pregnancy against COVID-19 hospitalization in infants.…”
mentioning
confidence: 99%